Bioimpedance measurement: a non-invasive diagnosis of limb compartment syndrome - Novak, Martin; Jecminek, Vladimir; Pleva, Leopold; Penhaker, Marek; Schmidt, Martin; Mimra, Tomas; Kubicek, Jan; Augustynek, Martin (Frontiers in Bioengineering and Biotechnology, 2024)
INTRODUCTION: The methods for diagnosing compartment syndrome non-invasively remain under debate. Bioimpedance measurements offer a promising avenue in clinical practice, detecting subtle changes in organ impedance due to volume shifts. This study explores bioimpedance measurement as a novel, painless method for diagnosing compartment syndrome, potentially enabling continuous monitoring. OBJECTIVE: This work aims to develop a prototype device for non-invasive diagnosis of compartment syndrome based on bioimpedance changes and assess initial results through in vitro experiments on inanimate biological material. We assume a change in the bioimpedance value after the application of physiological solution. MATERIALS AND METHODS: Between 2018 and 2022, a prototype device for diagnosing limb compartment syndrome was collaboratively developed with the Department of Cybernetics and Biomedical Engineering at the Technical University of Ostrava, Czech Republic. This device operates by comparing bioimpedance between two compartments, one of which is pathologically affected (experiencing compartment syndrome).The Bioimpedance Analyzer for Compartment Syndrome (BACS) has been utilized to conduct measurements on inanimate biological material in laboratory settings. Two samples of duck and chicken tissue, as well as piglets, were employed for these experiments. According to the size of sample was compartment syndrome simulated by injecting 20-120 ml saline into one limb (breast) while leaving the other as a control. Invasive intramuscular pressure measurements were conducted post-saline injection using a conventional device (Stryker). Changes in bioimpedance were evaluated following saline application.The non-invasive bioimpedance measurement instrument has been developed. It meets the safety requirements of European standard EN 60601-1. Measurement of accuracy showed minimal deviation for both channels (1.08% for the left channel and 1.84% for the right channel) when measuring on resistors. Ten measurements were conducted using the BACS prototype -two on chicken legs, two on duck breasts, two on duck legs, and four on piglets.Compartment syndrome simulation was achieved for all 10 measurements (IMP variance 31-45 mm Hg). Following saline application, a notable decrease in bioimpedance was observed in the compartment simulating compartment syndrome (decrease by 12-78 ).CONCLUSION: Non-invasive methods could revolutionize limb compartment syndrome diagnosis, offering advantages such as non-invasiveness and continuous monitoring of compartment swelling.